RESEARCH ON THE IMPACT OF THE HOSTILITIES IN UKRAINE ON TOURISM IN THE DANUBE DELTA - Romeo Cătălin CREȚU; Ioan Iulian ALECU; Ionuţ Silviu BEIA; Viorel Costin BANȚA; Petrică ȘTEFAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The purpose of the paper was to study the tourism in the Danube Delta and to evaluate the impact of the hostilities in Ukraine on tourist flows and other aspects. The study was carried out between February 5 and March 5 2024, by applying a questionnaire with 6 questions, on site and during the Romanian Tourism Fair (February 5- 8). The questions in the questionnaire addressed how the tourism structures in the Danube Delta have been affected by the hostilities in the neighborhood and whether they were helped by the central and local public authorities. Representatives of 78 accommodation units, totaling 3,080 accommodation places, as well as representatives of some public institutions and NGOs answered the questionnaire. It was tried to find out exact data from all areas of the Danube Delta, so the authors went to the representative localities from a tourist point of view: C.A. Rosetti, Letea, Periprava, Chilia Veche, Crisan, Mila 23, Jurilovca, Maliuc, Murighiol, Sfântu Gheorghe and Sulina. The conclusions pointed out a deep decline in the number of tourists in the Danube Delta in the year 2023, by 42% compared to 2022.